Growth Response and Production Of Eggplant (Solanum melongena L) with Dosage Test of Chicken Manure and Phospath Fertilizer - Helena Hasibuan (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
The low production of eggplant plants in Indonesia is due to the fact that the business of these plants is less intensive and is still traditional without intensive cultivation, especially in the use of fertilizers so that it can support the growth and yield of eggplant plants. Increasing production yields can also be done by means of fertilization using the right dose. The main function of fertilizer is to provide or add nutrients which are sometimes available in small quantities, or even not available at all in the soil. Organic chicken manure and inorganic phosphate fertilizers contain various types of nutrients and substances needed by plants. For this reason, it is necessary to find the appropriate dose used to obtain optimal growth and yield of eggplant plants. Research Objectives To determine the dose of chicken manure and phosphate fertilizer on the growth and yield of eggplant (Solanum malongena L). To determine the effect of chicken manure doses and phosphate fertilizer doses and the best interaction between chicken manure doses and phosphate fertilizer doses on the growth and yield of eggplant (Solanum malongena L). The experimental design used in this study was a factorial randomized block design (RBD) consisting of two treatment factors, namely: Factor I: Dosage of chicken manure (A) consisted of 3 levels, namely: A0= Kontrol, A1= 4 kg/plot (6 ton/ha), A2 = 6 kg/plot (8 ton/ha). Factor II: P0= Kontrol, P1= 4,5 g/plot, P2= 9,0 g/plo, P3= 13,5 g/plot. The results showed that the dosage of chicken manure was significantly different for plant height, number of primary branches, number of sample planting fruit, sample planting production and production per plot. The best dose of chicken manure in this study was A2 (6 kg/plot). Phosphate fertilizer dosage treatment was significantly different for plant height, number of primary branches, number of sample planting fruit, sample crop production and production per plot. The best dose of NPK fertilizer in this study was P3 (13.5 g/plot). The interaction between cow manure and phosphate fertilizer doses was not significantly different on plant height, number of primary branches, number of sample planting fruit, sample crop production and production per plot.